2017
DOI: 10.1002/cplu.201700524
|View full text |Cite
|
Sign up to set email alerts
|

An H2S‐Sensing/CO‐Releasing Flavonol That Operates via Logic Gates

Abstract: Signaling molecules, including H2S and CO, are involved in a complex interplay within cells to maintain cellular homeostasis. In order to investigate the intracellular interplay of different gasotransmitters, new molecular tools are needed that combine sensing and release capabilities of different small molecules in a single, multifunctional, and highly-regulated molecular platform. This report gives the first example of a combined H2S sensor/CO-releasing molecule. This flavonol-based molecular tool operates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 34 publications
(30 reference statements)
0
40
0
Order By: Relevance
“…The unmasking of the phenolic groups of 3-HF derivatives led to a large Stokes shi, which was previously used for the design of ratiometric uorescent probes. 51 Recently, Berreau and coworkers [32][33][34][35][36] ingeniously found that extended 3-HF derivatives could release CO under visible light irradiation. In this case, the uorescent extended 3-HF moieties were transformed into nonemissive 3-(benzoyloxy)-2-naphthalenecarboxylic acid (3-BNA) species, enabling self-reporting CO release.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unmasking of the phenolic groups of 3-HF derivatives led to a large Stokes shi, which was previously used for the design of ratiometric uorescent probes. 51 Recently, Berreau and coworkers [32][33][34][35][36] ingeniously found that extended 3-HF derivatives could release CO under visible light irradiation. In this case, the uorescent extended 3-HF moieties were transformed into nonemissive 3-(benzoyloxy)-2-naphthalenecarboxylic acid (3-BNA) species, enabling self-reporting CO release.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the hydroxyl groups of extended 3-HF have been successfully masked by thiol-, 35 H 2 S-, 36 and H 2 O 2 (ref. 37)-reactive moieties and photo-triggered CO release could be manipulated in a logical manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3‐hydroxyflavone and 3‐hydroxyquinolone photoCORM motifs are easily modified structures that can be customized for a variety of applications involving trackable CO delivery. These include sense and release applications wherein the CO‐releasing 3‐OH unit in 18 is unmasked for CO release only in the presence of a specific bioanalyte ,,…”
Section: Fluorescence Trackable Metal‐free Co‐releasing Molecules or mentioning
confidence: 99%
“…These include sense and release applications wherein the CO-releasing 3-OH unit in 18 is unmasked for CO release only in the presence of a specific bioanalyte. [32,33,35]…”
Section: Turn-off Photocorms Based On the 3-hydroxyflavone And 3-hydrmentioning
confidence: 99%